Nilai-Nilai Nasionalisme KH. Sholeh Darat Dalam Tafsir Faiḍ Al-Rahmān - M. Salsabily (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2021)
Nationalism is an understanding to love one's own nation and state and jointly defendand perpetuate the identity, integrity, prosperity, and strength of the nation itself. Oneof the scholars who have a nationalist spirit is KH. Sholeh Darat. In this paper, wewill discuss the values of KH's nationalism. Sholeh Darat in the interpretation of FaidAl-Rahman. In this paper, the author uses a type of library research, namely one of theworks of Faid Al-Rahmäān's commentary. The result of this research is that there arethree values of KH's nationalism. Sholeh Darat in Faid Al-Rahman's interpretation,namely the value of love for the homeland, the value of unity and unity and the valueof pluralism.